Effects of Hungarian water buffalo grazing on dry grasslands as a potential habitat management method - Fűrész, Attila; Fintha, Gabriella; Szentes, Szilárd; Wagenhoffer, Zsombor; Szalai, Ferenc; Penksza, Károly (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
Nowadays, the sustainability of agricultural fields has become a significant issue due to the impacts of climate change. Grazing livestock, such as Hungarian water buffalo, can have a very important role in the sustainability of these areas. Our aim in this research was to compare vegetation data from several years of domestic water buffalo grazing in the areas of Szurdokpüspöki by using cenological surveys, to monitor vegetation changes based on relative ecological indicators, conservation values. The surveys were carried out in three sample areas where there have been removing shrubs for 2, 4 and 6 years. Both the amounts and cover of economically important grasses and legumes increased. The high proportion of shrubs has shifted towards grassland species. Festuca valesiaca was the dominant species. According to Pignatti’s life-form system, the area was not overgrazed. The results showed that the grazing by domestic water buffalo was successful for both conservation and economic reasons. Supported by the ÚNKP-22-3-I-MATE/2 New National Excellence Program of the Ministry for Culture and Innovation from the source of the National Research, Development and Innovation Fund, and AKGF-119-1-202.